PREVENTION AND TREATMENT OF RADIODERMATITIS: AN INTEGRATIVE REVIEW - Franciane Schneider; Edivane Pedrolo; Jolline Lind; Alessandra Amaral Schwanke; Mitzy Tannia Reichembach Danski (Universidade Federal do Paraná, 2013)
The aim was to survey technologies for the prevention and/or treatment of radiodermatitis in patients with cancer of the head and neck. An integrative review was undertaken of the literature in the month of July 2011 in the following databases: the National Library of Medicine and Latin American and Caribbean Health Sciences, using the PICO strategy (Population, Intervention, Comparison, and Outcomes) for searching for articles which respond to the guiding question. Five articles were obtained. The results of the clinical trials did not raise significant differences in the use of the products or cares in the prevention and/or treatment of radiodermatitis in cancer of head and neck; the only study which concluded a product to be efficacious was carried out without comparisons. It is inferred that there is no scientific evidence for the introduction of a product/care measure for the prevention and/or treatment of radiodermatitis based on the results of this study.